Are the investors moonstruck? moon phases effect on stock index in India, Malaysia, Singapore and China / Mohd Hamizan Yabsah - Yabsah, Mohd Hamizan (2016)
This paper studies the effect of moon phases on the stock index in 4 countries which is India, Malaysia, Singapore and China. This study investigate if there is any impact of moon phases towards the stock index due to the Chinese population that live in these 3 countries which is Malaysia, Singapore and China. While India being selected as there is none Chinese people live in there. Hence, India being chooses to make comparison. On the other hand, Chinese people are belief in the feng shui, by looking into the Chinese Lunar Calendar. This study is to determine the different of moon phase’s effect between these 4 countries towards the stock index. Sample of data consists of range of Chinese population in different countries, moon phase’s calendar and the closing price. This study using time series analysis and the software used is Eviews. In order to carry out result, Single Regression was used to obtain Average Return. Meanwhile, EGARCH was used to measure to volatility of stock return. An event window is form for the measurement of moon phases.